Comparison of the Ability of Salicylic Acid and Ferricyanide to Induce Flowering in the Long-day Plant, Lemna Gibba G3 - Tanaka, Osamu (1980)
Both salicylic acid and ferricyanide induce flowering in the long-day plant Lemna gibba L., strain G3 under 8- and 9-hour short days. In both cases the effect is daylength-dependent. Salicylic acid is ineffective on daylengths less than 8 hours and ferricyanide is ineffective on daylengths less than 5 hours. When both substances are given together a striking synergistic interaction is observed, and some flowering is obtained on daylengths as short as 3 hours. However, even with the optimal combinations the flower-inducing effect remains daylength-dependent. Flowering of L. gibba G3 is inhibited under continuous light in both half-strength Hutner's medium (0.5 H), which contains 1.25 millimolar ammonium, and in ammonium-free half-strength Hutner's medium (NH(4)(+)-free 0.5 H). Salicylic acid is able to reverse the inhibition substantially in 0.5 H medium and to cause complete reversal in NH(4)(+)-free 0.5 H medium. By contrast, ferricyanide has no effect in 0.5 H medium and causes only a small reversal in NH(4)(+)-free 0.5 H medium. Flowering of L. gibba G3 is also inhibited under continuous light by copper. This inhibition is largely reversed by salicylic acid but ferricyanide has no effect.